THE INFLUENCE OF THE SHOPEE PAY LATER FEATURE, LIVE STREAMING, AND LIFESTYLE (HEDONIC MOTIVATION) ON THE CONSUMER BEHAVIOR OF PEOPLE IN PONTIANAK IN ONLINE SHOPPING - Riawan, Joni; -, Noviansius; Alvincia, Velissa; -, Vinsensius (Jurnal Manajemen Bisnis dan Terapan, 2025)
Increasing online purchasing practices have driven the growth of E-commerce in Indonesia. Based on the popularity of Shopee in Indonesia, payment methods have been developed to facilitate the consumer transaction process. Later, with the increased use of live streaming features and payment methods such as Shopee PayLater, Indonesia's hedonistic lifestyle is increasingly dominating consumer behavior. Finally, a hedonistic lifestyle significantly impacts Indonesian people's consumer behavior, especially among the younger generation and the upper middle class. Hedonistic motivation drives individuals to consume based on functional needs and gain emotional satisfaction and social status. This study will discuss in more depth the causal relationship that can be caused by the Shopee Pay Later feature (X1), Live Streaming (X2), and Hedonism Motivation (X3) on consumer shopping behavior (Y) by using a research method based on the results of the multilinearity test. It is concluded that the live streaming feature and hedonistic lifestyle have significantly influenced the Pontianak community's consumer behavior. In contrast, the Shopee Pay Later feature is not significant. This can be proved by the T-Test score, which shows that the Shopee Pay Later feature obtained a Sig result of 0.680, which means it does not affect consumer behavior. Meanwhile, the Live Streaming feature obtained a Sig result of 0.005, and the hedonistic lifestyle shows a Sig result of 0.000, which means that these two variables have a significant effect in line with the research results. In addition, a hedonistic lifestyle strengthens the emotional drive to shop to achieve personal satisfaction.